2020
DOI: 10.1103/physrevb.101.035407
|View full text |Cite
|
Sign up to set email alerts
|

Real-space investigation of the charge density wave in VTe2 monolayer with broken rotational and mirror symmetries

Abstract: Recently the charge density wave (CDW) in vanadium dichalcogenides have attracted increasing research interests, but a real-space investigation on the symmetry breaking of the CDW state in VTe2 monolayer is still lacking. We have investigated the CDW of VTe2 monolayer by low energy electron diffraction (L D) and scanning tunneling microscope (STM). While the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Recently, there has been much progress in the experimental synthesis of vanadium dichalcogenides, a class of materials with exotic physical properties, such as charge‐density‐wave behavior and robust room‐temperature ferromagnetism . VTe 2 , which shows more complicated phases and thus rich phase‐transition phenomena, has been gaining increasing attention . As another test case, we model a T‐VTe 2 CS‐FET.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been much progress in the experimental synthesis of vanadium dichalcogenides, a class of materials with exotic physical properties, such as charge‐density‐wave behavior and robust room‐temperature ferromagnetism . VTe 2 , which shows more complicated phases and thus rich phase‐transition phenomena, has been gaining increasing attention . As another test case, we model a T‐VTe 2 CS‐FET.…”
mentioning
confidence: 99%
“…[43][44][45] VTe 2 , which shows more complicated phases and thus rich phase-transition phenomena, has been gaining increasing attention. [46][47][48][49] As another test case, we model a T-VTe 2 CS-FET.…”
mentioning
confidence: 99%
“…8 of Appendix E). This pseudogap was initially explained in terms of CDW fluctuations in the previous ARPES study 28 , whereas the subsequent STM and LEED experiments 30,31 reported the 4×4 CDW and attributed the pseudogap to the CDW gap due to the FS nesting in the flat segments of triangular FS 30 (see also Appendix E). We found from the analysis of reflectionhigh-energy-electron-diffraction (RHEED) patterns that the 1T ' structure is immediately formed when the film thickness reaches 2ML during epitaxy (see Fig.…”
Section: Energy Gap and Cdwmentioning
confidence: 95%
“…Bulk VTe 2 forms the monoclinic 1T " phase with 3×1×3 PLD and undergoes a structural transition to the polymorphic 1T structure at T = 482 K [25][26][27] . On the other hand, monolayer VTe 2 stabilizes with the 1T structure [28][29][30][31][32][33] and exhibits the 4×4 CDW [25][26][27] . Although the relationship between fermiology and PLD as well as the origin of different crystal structures between monolayer and bulk have been intensively discussed, these key questions 34,35 are still controversial [34][35][36][37] .…”
Section: Introducitonmentioning
confidence: 99%
“…In experiment, an angle-resolved photoemission spectroscopy (ARPES) study revealed that the CDW order opens an anisotropic gap near the Fermi level [17]. The microscopic images of CDW modulations obtained with scanning tunneling microscope (STM) show different phase shifts relative to the lattice implying an inter-unit-cell distribution of orbitals [16,[18][19][20]. These experimental findings suggest a nonuniform distribution of the CDW orders in real space.…”
mentioning
confidence: 99%